Social Organizations, Violence & Modern Growth - Avner Greif; Murat Iyigun (Institute for the Study of Labor (IZA), 2013)
Although social institutions permeate the world in which we live, they are all but absent from our analyses of economic growth and development. This paper argues the need to mitigate this omission by demonstrating the importance of social institutions for growth and development.
Keywords: O10; N10; N13; 330; institutions; economic development